Hypertension Counseling and Tomato Juice Provision to Lower Blood Pressure in Hypertension Patients in Suka Sari Village, Hamlet 02, Semarang, Kebawetan Subdistrict, Kepahiang Regency - Ria Emalyanda; Feny Triyany; Suci Rohima Janista; Reni Parida; M Syahrul Hamdi; Diyah Tepi Rahmawati; Hengky Tranado; Janista Janista (Jurnal Pengabdian Mandiri, 2026)
Hypertension is a common health problem faced by many people and requires simple management that can be carried out independently. The activity "Counseling and giving tomato juice to lower blood pressure in hypertensive patients" by KKN-T students of Dehasen University Bengkulu was held in Suka Sari Village, Kebawetan District, Kepahiang Regency on Thursday, November 4, 2025. This activity aims to increase community knowledge about hypertension management and provide a healthy drink alternative in the form of tomato juice to help lower blood pressure. The method used was a pre-post test conducted in one day. The results of the activity showed an increase in understanding of how to manage hypertension. This activity is expected to become a simple effort that the community can apply to help control blood pressure independently.